Comparative cytotoxic activity of Convolvulus pluricaulis against human hepatoma cell line (HepG2) and normal cell line (L929) via apoptosis pathways by flow cytometry analysis - Ashpak Mubarak Tamboli; Kiran Anna Wadkar (Bulletin of the National Research Centre, 2022)
Abstract Background The purpose of this study was to use the MTT test to assess the cytotoxic effects of different extracts of Convolvulus pluricaulis leaves in vitro. Convolvulus pluricaulis leaf ethanolic extract has been demonstrated to trigger apoptosis on HepG2 cancer cell lines, implying anti-cancer activity. Methods The cells were grown in culture DMEM and incubated with different concentrations of the plant extracts. Survival rates were quantified by MTT assays by 24 h of exposure to (640–20 µg/ml) the PEE, CHCl3E, EAE, ETHE and AQE of the plant, while monitoring changes on cellular shapes by inverted phase contrast microscopy (PEE—petroleum ether extract, CHCl3—chloroform extract, EAE—ethyl acetate extract, ETHE—ethanol extract, AQE—aqueous extract). Results The Convolvulus pluricaulis leaves extract showed IC50 value < 1000 μg/ml on HepG2 and IC50 value > 1000 µg/ml on L-929 cell lines. Hence, Convolvulus pluricaulis leaves extracts are non-toxic against the normal cell line L-929. Treatments with standard as a control exhibited necrotic features in both cell lines. On the basis of these findings, and because a highly effective extract ETHE has a partial polarity, this plant cytotoxicity and apoptotic activities were also investigated. On HepG2 cell line, the ETHE showed higher cytotoxicity activities compared to AQE, EAE, CHCl3E, and PEE extracts (P < 0.0001) with inhibitory concentration IC50 values of 35.873 μg/ml that is < 1000 μg/ml. The percentage of apoptotic cells of ETHE was determined using propidium iodide (PI) staining of DNA fragments by flow cytometry. Conclusions The extract of Convolvulus pluricaulis has cytotoxic and apoptotic action against the HepG2 cell line, indicating that it should be studied further for cancer therapies.